Faulkner : masks and metaphors - Hönnighausen, Lothar (University Press of Mississippi, 1997)
That Faulkner was a "liar" not just in his writing but also in his life has troubled many critics. They have explained his numerous "false stories," particularly those about military honors he actually never earned and war wounds he never sustained, with psychopathological imposture-theories. The drawback of this approach is that it reduces and oversimplifies the complex psychological and aesthetic phenomenon of Faulkner's role-playing. Instead, this critical study by one of the most acclaimed international Faulkner scholars takes its cue from Nietzsche's concept of "t